2023
DOI: 10.1590/1413-81232023284.14132022
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à qualidade do sono de estudantes universitários

Abstract: Resumo Investigar fatores associados a pior qualidade do sono. Estudo transversal realizado em 2019, com amostragem aleatória sistemática. Informações sobre sono foram obtidas através do Mini Sleep Questionaire (MSQ). Variáveis independentes incluíram características sociodemográficas, comportamentais, acadêmicas e de saúde psicológica. Análises ajustadas foram feitas com regressão de Poisson. Participaram 996 estudantes de graduação. A pior qualidade de sono atingiu 23,1% da amostra (IC95% 20,5-25,9), oscilan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
1
0
2
Order By: Relevance
“…university students, as is the case of a study carried out in northeastern Brazil on 209 students in 2018, in which they observed severely altered sleep. The same students showed greater changes in cardiovascular risk factors analyzed about students with normal sleep, with a positive relationship between sleep quality and all factors investigated (7) .Other studies with university students have demonstrated a diversity of influences on sleep quality, including psychosocial, environmental and behavioral factors (8,9) . Furthermore, during the COVID-19 pandemic, education systems were affected, where university students in distance learning noticed a worsening in their sleep quality, a reduction in the practice of physical activities and an increase in the use of electronic devices in the preceding hour.…”
mentioning
confidence: 63%
“…university students, as is the case of a study carried out in northeastern Brazil on 209 students in 2018, in which they observed severely altered sleep. The same students showed greater changes in cardiovascular risk factors analyzed about students with normal sleep, with a positive relationship between sleep quality and all factors investigated (7) .Other studies with university students have demonstrated a diversity of influences on sleep quality, including psychosocial, environmental and behavioral factors (8,9) . Furthermore, during the COVID-19 pandemic, education systems were affected, where university students in distance learning noticed a worsening in their sleep quality, a reduction in the practice of physical activities and an increase in the use of electronic devices in the preceding hour.…”
mentioning
confidence: 63%
“…O sono é essencial para a manutenção da vida e pode ser definido como o período em que o estado de vigília encontra-se suspenso, ocorrendo redução das atividades metabólicas, relaxamento muscular e diminuição das atividades sensoriais 1 . Além disso, tem importantes funções biológicas na consolidação da memória, termorregulação e restauração do metabolismo energético cerebral 2 .…”
Section: Introductionunclassified
“…Em um estudo com universitários do México, 42,8% relataram dormir menos de oito horas por noite e apenas 13% disseram ter e respeitar um horário para dormir e acordar (Campas et al, 2020). É importante que sejam desenvolvidas ações de promoção da qualidade do sono na população universitária por meio de abordagens psicossociais e fortalecimento de habilidades socioemocionais e outras estratégias que minimizem os problemas que possam atrapalhar o sono (Maciel et al, 2023). Contudo, também é preciso analisar as condições de moradia digna, sobrecarga e outras situações ligada ao contexto de vida e estudo dos estudantes.…”
Section: Discussionunclassified